(untitled) (Journal of Forestry, 2024)
Today, it is mandatory for all employers to conduct risk analysis because of legal regulations and the increased importance attached to occupational safety and health (OSH) by society. Each harvesting unit has a unique topography, climate, type of machine or equipment, tree species, harvesting time (summer/winter), and external threats. Therefore, it is necessary to carefully identify the potential risks for each harvesting unit. This study compared the risk scores of forest harvesting in the Black Sea, Mediterranean, Aegean, Marmara, and Southeastern Anatolia regions of Türkiye with different geographical conditions. The risk analysis was conducted with a total of 338 harvesting workers from these regions. Twenty-nine hazards, categorized into six main classes, were identified via literature review, field observations, and expert opinions. Risk analysis was performed using the L-type matrix method. After that, the Chi-square test analyzed whether the risk scores determined for each geographic region differed or not. The results revealed significant differences in the results of risk analyses of harvesting activities between regions (c2 = 97.357; p<.001). While these differences were determined generally in the physical, psychosocial, and worker-related hazard classes, an obvious difference in biological or chemical hazard classes was not determined statistically. The results of the risk analysis obtained from the study will contribute to the identification of the risks that should be taken into consideration primarily for the examined regions and the implementation of measurements. Moreover, this study serves as a model for conducting risk analysis for other regions, to facilitate informed decision-making concerning OSH.